Functional Outcome in Distal Femoral Fractures Treated by Locking Compression Condylar Plates: A Short Term Prospective Study - Pugazhendhi, G.; Venkatachalam, K.; Madhukar, . (Recent Developments in Medicine and Medical Research Vol. 15, 2021)
Treatment of distal femoral fractures, whether with or without comminution or intra-articular extension, has always been challenging. Hardware breakdown is an issue among the elderly, especially in those with osteoporosis. The functional prognosis of 22 cases treated with locking compression condylar plates is examined in this prospective study. It was decided to use the OTA classification system. The functional outcome analysis was conducted using Neers' functional scoring system. The 22 cases took an average of 16 weeks to reach a sound union (14 to 20weeks). Locking compression condylar plates provide robust fixation in carefully selected instances, resulting in sound union and consistently good functional knee movement.